Prinsip-Prinsip Penataan Tapak Perumahan Masyarakat Adat - Ninik Dwi Resky; Shirly Wunas; Mimi Arifin (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2018)
The traditional village is a traditional settlement that has a tradition that is still maintained today such as Maudu Lompoa, which is conducted once a year and is used as cultural tourism in South Sulawesi. This encourages the growth of settlements around the space of cultural activities that can reduce the carrying capacity of housing areas. This study aims to identify the physical characteristics of housing spatial patterns and their development in terms of local wisdom, housing layout is reviewed in terms of the social and economic strata of the community and explains the principles of structuring the housing layout of indigenous peoples. The data collection techniques are by observation, interview, documentation, literature study, questionnaire distribution and institutional data collection. The analytical method used is descriptive qualitative, comparative, spatial and grid index analysis. The results showed that the development of housing followed the space around the space of cultural activities. Permanent use of cultural activities. Housing patterns are tied to the space of cultural activities. The housing layout tends to follow the kinship groups or develop around cultural space. Some site arrangements tend to spread beyond a 500-meter radius of the cultural activity space or develop following the existing road network. The principles of structuring the sites of indigenous peoples' housing, namely, the principle of structuring conservation areas around the space of cultural activities and the principle of structuring areas outside a 500-meter radius, can be developed because there is still a large enough open land.